O pincel e a pena na construção da nação: pintando e narrando um mito político fundacional - Susana Bleil de Souza (Les Cahiers ALHIM)
It is our intention to examine the role of the painting and the literature in the construction process of an Uruguayan national identity by the intellectual and political elite throughout the second half of the 19th century and the beginning of the 20th century. This was the consolidation period of the modern state apparatus in the country as well as the beginning of an historical and graphical national tradition. As Uruguay conquered its independence from Brazil through successive wars, the Uruguayan elite was faced with a need to reinvent an independent country free from the threats of the Imperial Brazil. The nation needed to construct itself as homogeneous, consensual, a meaningful community with a collective project which, based on a past of bravery, could project the nation towards a grand future, to which it was predestinated since the beginning. In this context the works of two authors will be examined: the historical novels from Eduardo Acevedo Díaz as a political-pedagogical instrument and the pictorial representations of Juan Manuel Blanes.